Worker Protection Standard (WPS) Responsibilities and Compliance - Emily Kraus; Brett Bultemeier (EDIS)
The purpose of this new 10-page publication of the UF/IFAS Pesticide Information Office is to assist Extension agents and agricultural stakeholders themselves to understand what the Worker Protection Standard (WPS) is, what the individual requirements are for different roles, and overall, how to comply with the requirements of WPS. This document is a highly condensed version of the law and is intended to help agents and stakeholders find the full list of requirements in a much larger, more difficult-to-digest document from the EPA. Written by Emily Kraus and Brett Bultemeier. https://edis.ifas.ufl.edu/pi294